ENHANCING COMMUNITY WELFARE THROUGH SHARIA MANAGEMENT IN MICRO WAQF BANKS: A PROPOSED COMPARATIVE STUDY OF MALAYSIA AND INDONESIA - Ab Rahman , Siti Maziah; Shaari , Rustam; Nik Din , Nik Muniyati; Abdul Wahid , Khalid; Mohd Zaki , Adeeba Najihah; Yasin, Ahmad Bukhari (Journal of Islamic, Social, Economics and Development, 2024)
This study aims to analyze and compare the implementation of Sharia compliance in the business activities of Micro Waqf Banks in Malaysia and Indonesia as an effort to enhance community welfare. Micro Waqf Banks are Islamic microfinance institutions that provide access to capital and financing for low-income communities who lack access to formal financial institutions. The research will apply a qualitative approach with statutory and conceptual analysis. Micro Waqf Banks are required to implement sharia compliance in their operations to protect the spiritual rights of Muslim consumers and build credibility as Islamic financial institutions. This includes using Sharia-compliant contracts, avoiding prohibited elements like interest, and aligning with Islamic principles. However, the regulatory frameworks differ between Malaysia and Indonesia. Malaysia has more comprehensive regulations on sharia governance for Islamic financial institutions, while Indonesia's regulations are spread across various laws and regulations. Despite this, both countries demonstrate a commitment to ensuring Sharia compliance in Micro Waqf Banks to promote financial inclusion and improve the welfare of the underprivileged communities they serve. The study provides insights into best practices and areas for improvement in the Sharia-based management of Micro Waqf Banks to enhance their social impact.